Pertumbuhan sektor pertanian dan penyerapan tenaga kerja di Jawa Tengah - Santoso, Rokhedi Priyo; Sobirin, Sahrul (Jurusan Ilmu Ekonomi, Fakultas Bisnis dan Ekonomika, Universitas Islam Indonesia, 2025)
Purpose – This study aims to analyze the impact of agricultural sector growth on its labor absorption in Central Java Province from 2019 to 2023Methods – Labor absorption in the agricultural sector is regressed against agricultural sector growth, labor force participation rates, and minimum wage using static panel data analysis methods. After going through model selection procedures, the best estimation model is the fixed effect model. Findings – The study's results indicate that labor absorption in the agricultural sector is not influenced by the growth of the agricultural sector itself due to efficiency and mechanization in this sector. On the contrary, the level of labor absorption follows the developments in labor force participation rates and the minimum wage at the district/city level. This indicates that labor in the agricultural sector comprises of workers who are not absorbed in the formal sector.Implication – The increase in productivity in the agricultural sector is expected to enhance labor absorption in this sector through the intensification and extensification of agriculture.Originality – This research has strategic value in increasing labor absorption in the agricultural sector to reduce unemployment in Indonesia. AbstrakTujuan – Penelitian ini bertujuan untuk menganalisis pengaruh pertumbuhan sektor pertanian terhadap penyerapan tenaga kerjanya di Propinsi Jawa Tengah periode 2019 - 2023.Metode – Penyerapan tenaga kerja sektor pertanian diregress terhadap pertumbuhan sektor pertanian, tingkat partisipasi angakatan kerja, dan upah minimum dengan menggunakan metode analisis panel data statis. Setelah melalui prosedur pemilihan model maka model estimasi yang paling baik adalah fixed effect. Temuan – Hasil studi menunjukkan bahwa penyerapan tenaga kerja di sektor pertanian tidak dipengaruhi oleh pertumbuhan sektor pertanian itu sendiri yang diduga karena efisiensi dan mekanisasi sektor pertanian. Sebaliknya, tingkat penyerapan tenaga kerja mengingkuti perkembangan tingkat partisipasi angkatan kerja dan tingkat upah minimum kabupaten/kota. Hal ini mengindikasikan bahwa tenaga kerja sektor pertanian merupakan angkatan kerja yang tidak terserap pada sektor formal.Implikasi – Peningkatan produktivitas sektor pertanian diharapkan dapat meningkatkan penyerapan tenaga kerja pada sektor ini melalui intensifikasi dan ekstensifikasi pertanian.Orisinalitas – Penelitian ini memiliki nilai strategis dalam meningkatkan penyerapan tenaga kerja di sektor petanian untuk mengurangi pengangguran di Indonesia.